2008
DOI: 10.3844/ajassp.2008.209.220
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Ductility of Randomly Distributed Palm Fibers Reinforced Silty-Sand Soils

Abstract: This paper investigates the resultant strength and ductility behavior when randomly distributed palm fibers are used to reinforce silty-sand soils. The composite soils were tested under laboratory conditions and examined for unconfined compression strength (UCS), California Bearing Ratio (CBR) and compaction test. The results indicated that; the maximum and residual strengths, orientation of surface failures, ductility and the stress-strain relationship of the specimens were substantially affected by the inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(53 citation statements)
references
References 23 publications
6
38
0
1
Order By: Relevance
“…Nagrale et al (2005) studied the improvement of CBR value of subgrade soil with inclusion of polypropylene fibers and concluded that 1.5% fiber with aspect ratio 100 and 84 would be the optimum quantity in clayey soil and fine sand respectively. Marandi et al (2008) studied the strength and ductility of fiber reinforced silty sand with palm fibers and concluded that palm fibers could be used as a reinforcing material in improving the strength and ductility characteristics of soil. Jadhao and Nagarnaik (2008) studied the influence of polypropylene fibers on the engineering behavior of soil fly ash mixtures by using different fiber lengths (6, 12 and 24 mm) in the range of 0-1.5% by dry wet of soil and observed that maximum improvement in strength was achieved at a fiber length of 12 mm with fiber content of 1%.…”
Section: Introductionmentioning
confidence: 99%
“…Nagrale et al (2005) studied the improvement of CBR value of subgrade soil with inclusion of polypropylene fibers and concluded that 1.5% fiber with aspect ratio 100 and 84 would be the optimum quantity in clayey soil and fine sand respectively. Marandi et al (2008) studied the strength and ductility of fiber reinforced silty sand with palm fibers and concluded that palm fibers could be used as a reinforcing material in improving the strength and ductility characteristics of soil. Jadhao and Nagarnaik (2008) studied the influence of polypropylene fibers on the engineering behavior of soil fly ash mixtures by using different fiber lengths (6, 12 and 24 mm) in the range of 0-1.5% by dry wet of soil and observed that maximum improvement in strength was achieved at a fiber length of 12 mm with fiber content of 1%.…”
Section: Introductionmentioning
confidence: 99%
“…Pavements constructed on reinforced subgrades have several advantages from economic, environmental and traffic safety point of view (Marandi et al 2008). It allows thinner road structures and prolonged life cycles, which lead to a saving in natural resources.…”
Section: Necessity For Reliability Based Designmentioning
confidence: 99%
“…In fiber-reinforced uncemented soil, interactions occur at the interface between the fiber surface and the clay grains that play key role in the mechanical behavior. Marandi et al (2008) used natural palm fibers as soil reinforcement. Fiber contents used were 0.25%, 0.50%, 0.75%, 1.00%, 1.5%, 2.00% and 2.50% by dry total weight whereas the fiber lengths tested were 20 mm and 40 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Findings show that coir fibre exhibits greater enhancements in the strength of soil by having higher coefficient of friction [12]. Coir retains much of its tensile strength when wet and it has low tenacity but the elongation is much higher [13] and as for palm fiber, a constant palm fiber length, with increase in fiber inclusion, the maximum and residual strengths were increased [14]. It is observed that the palm fibers act to interlock particles and group of particles in a unitary coherent matrix thus…”
Section: Shear Strength Propertiesmentioning
confidence: 99%